أثر استراتيجية التعليم المتمايز في التحصيل لدى تلميذات الصف الخامس الابتدائي في مادة الاجتماعيات (Journal of the College of Basic Education, 2020)
The present research aims at identifying the effect of the differential learning strategy on the achievement of the students of the fifth grade in social studies. To achieve the research objective, the researchers put the following hypothesis:There were no statistically significant differences at (0.05) between the average score of the experimental group students who studied the social subject with the differentiated education strategy and the average grade of the control group who studied the same material in the traditional way in the achievement test.The two researchers chose the Directorate General for the third Rusafa education in a radical way to apply the research and also chose the primary form of light (for girls) to conduct the experiment. The students of the two groups were randomly selected. The researchers studied the two research groups. The researchers prepared a 30- The results were treated statistically using the T test and two independent samples. The results showed that the students in the experimental group who study social subjects were superior to the students of the control group who study the same subject in the traditional way in the achievement test.In light of the results of the research, the researchers recommend the following: The need to use social teachers and teachers strategies and teaching models in the teaching and teaching of social subjects, especially the distinctive education strategy, which proved its effectiveness through the current research.Proposals:1-Conduct a comparative study between the impact of the differentiated education strategy and other educational strategies in the achievement of other stages of study.2- Conduct a study on the impact of the differentiated education strategy in other dependent variables such as critical, creative, scientific and interpretative thinking.